Clinical characteristics of combined rosacea and migraine - Wienholtz, Nita K. F.; Christensen, Casper E.; Zhang, Ditte G.; Rechnagel, Anne-Sofie A.; Byrnel, Helene V. S.; Haugaard, Jeanette H.; Ashina, Messoud; Thyssen, Jacob P.; Egeberg, Alexander (Frontiers in Medicine, 2022)
Background: An overlap between the skin disease rosacea and the headache disease migraine has been established; however, the magnitude of this overlap and the distribution between subtypes/phenotypes remains unclear. Objective: The aim was to determine the magnitude of the overlap between rosacea and migraine, and to determine which subtypes/phenotypes were present in patients with concomitant rosacea and migraine. Methods: In this cross-sectional study, 604 patients with a diagnosis of either rosacea or migraine were phenotyped through a face-to-face interview with clinical examination, to determine prevalence and phenotype of rosacea, and prevalence and subtype of migraine. Results: We found a prevalence of migraine of 54% in patients with rosacea, and a prevalence of rosacea of 65% in patients with migraine. Concomitant migraine was significantly associated with the rosacea features flushing (odds ratio = 2.6, 95% confidence interval = 1.4 – 4.7, p = 0.002), ocular symptoms (odds ratio = 2.4, 95% confidence interval = 1.5 – 3.9, p < 0.001), and burning (odds ratio = 2.1, 95% confidence interval = 1.3 – 3.4, p = 0.002), whereas papules/pustules were inversely related with concomitant migraine (odds ratio = 0.5, 95% confidence interval = 0.3 – 0.8, p = 0.006). No association was found between concomitant migraine and centrofacial erythema, rhinophyma, telangiectasia, edema, or dryness. Concomitant rosacea was not associated with any specific migraine subtype in patients with migraine. Conclusions: This study highlights a substantial overlap between rosacea and migraine, particularly in patients with certain rosacea features. Individuals with rosacea should be asked about concomitant migraine, and comorbidities should be considered when choosing between treatments.